Hannah Arendt, education, and the question of totalitarianism. Issue 1 (2nd January 2016) - Spector, Hannah
Abstract : The aim of this paper is to consider the ways in which Arendt's writings on totalitarianism act as a warning sign for political and miseducational circumstances in the USA. Because the term totalitarianism has been used imprudently (largely in the mass media) to express repressive conditions in so-called models of democracy, this paper seeks to both clarify and raise questions concerning its meaning as a form of nation-state-sanctioned power and/or economic-technological force. This analysis draws largely from Arendt's definition of totalitarianism expressed as an antipolitical phenomenon characterized by terror-ruled ideological indoctrination which destroys both the public realm and the private identities. I contend that analyses of twentieth-century totalitarianism are significant to today's unprecedented questions and circumstances germinating in and having significance beyond the USA. I also describe the difficulty of action under extreme conditions. In the last analysis, I deliberate on the site of education as a totalitarian coercion.